2020
DOI: 10.1186/s13075-020-02369-8
|View full text |Cite|
|
Sign up to set email alerts
|

Cyr61 synthesis is induced by interleukin-6 and promotes migration and invasion of fibroblast-like synoviocytes in rheumatoid arthritis

Abstract: Background Interleukin-6 (IL-6) is involved in fibroblast-like synoviocyte (FLS) activation and promotes pannus formation and bone and cartilage destruction in rheumatoid arthritis (RA). Cysteine-rich 61 (Cyr61) protein regulates cell proliferation, migration, and differentiation. The aim of this study was to investigate the role of Cyr61 in RA-FLS migration and invasion after IL-6 stimulation. Methods Western blotting, immunohistochemistry, reverse transcription-polymerase chain reaction, and real time-polym… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…In our work the levels of MMP1 mRNA in groups incubated with IL-6 and with IL-6 in presence curcumin were substantially lower than in the control. These outcomes seem to corroborate the results obtained by Choi et al [ 27 ], proving that IL-6 does not increase MMP-1 production in synoviocytes.…”
Section: Discussionsupporting
confidence: 91%
“…In our work the levels of MMP1 mRNA in groups incubated with IL-6 and with IL-6 in presence curcumin were substantially lower than in the control. These outcomes seem to corroborate the results obtained by Choi et al [ 27 ], proving that IL-6 does not increase MMP-1 production in synoviocytes.…”
Section: Discussionsupporting
confidence: 91%
“…Liu once reported that Sonic Hedgehog (SHH) signaling pathway mediates migration of RA-FLSs via MAPK/ERK pathway and may contribute to the progression of RA ( Liu et al, 2018 ). Choi also revealed that IL-6-regulated Cyr61 is a key player in FLS migration and invasion and eventually contributes to joint destruction in RA ( Choi et al, 2020 ). Similarly, our results also validated that ATF3 overexpression could promote the migration of RA-FLSs, while knockdown of ATF3 reduced the migration ability of FLSs.…”
Section: Discussionmentioning
confidence: 99%
“…CCN1 and CCN2 have similar roles in RA pathogenesis, as both favour fibroblast-like synoviocite proliferation and induce osteoclastogenesis as well as angiogenesis (Chen et al 2017a , 2017b ; Ding et al 2016 ; Ganesan and Rasool 2017 ; Nozawa et al 2009 ; Zhang et al 2009 ). Moreover, CCN1 induces the expression of the proinflammatory cytokine IL-6 (Choi et al 2020 ; Lin et al 2012 ), IL8 and CCL20 which promote neutrophil and monocyte migration to the synovium (Chen et al 2017a ; Zhu et al 2015 ), and MMPs, which foster cell migration (Kwon et al 2017 ).…”
Section: Ccn Proteins In Degenerative and Inflammatory Diseases Of The Musculoskeletal Systemmentioning
confidence: 99%